The Prevalence of Polycystic Ovarian Syndrome in Students of Sir Syed Medical College for Girls, Karachi - SONIA NAQVI, EMAN KHALID, ANISA KAMAL (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the prevalence of Polycystic Ovarian Syndrome in students of Sir Syed Medical College for Girls. Study Design: Descriptive, Cross-Sectional Study. Place and Duration: Outpatient Department of Sir Syed Hospital from August 2012 - December 2012. Methodology: One hundred and thirty eight students were enrolled in the study after informed consent. The information about study variables was collected by administering a predesigned questionnaire. The data was based on demographic, body mass index(BMI), relevant biochemical tests and abdominal ultrasound evaluation. Results: Eighty four students revealed familial tendencies. All these students presented with symptoms, i.e., menstrual Irregularities and pelvic pain in 30.2% and 32.4% respectively, hirsutism was another challenging symptom met by the 15.8% of respondents . An advancing symptom debated was weight gain which was reported by 7.9% participants. Thyroid dysfunction was found to be 14.4%; whereas serum insulin tested positive for 30.2%. BMI showed that underweight 27.3%. 46% were overweight and 23% obese. Conclusion: The Prevalence of Polycystic Ovarian Syndrome(PCOS) is high in students of Sir Syed Medical College. It can be predicted reliably with the help of history, clinical features, laboratory investigations and sonography